Sitem Subak Sebagai Sumber Belajar IPAS dalam Pendidikan di Bali : Sistem Subak Sebagai Sumber Belajar IPAS dalam Pendidikan di Bali - Sriariani, Ni Luh Made; I Wayan Lasmawan; I Wayan Kertih (JPG: Jurnal Pendidikan Guru, 2025)
The purpose of this study was to analyze the science and social studies (IPAS) learning materials that can be inserted with Balinese subak local wisdom. This research method is a literature review by analyzing materials and articles that have been published over the past five years. The results of the study are that science and social studies learning in Bali stages C and D can be inserted with Balinese subak local wisdom in the material on the geographical conditions of the residential environment. Research articles that discuss subak local wisdom in learning include five articles consisting of pre-experimental research, development of videos and teaching materials, and literature reviews. The conclusion of this study is that the materials that can be inserted with subak local wisdom are the geographical conditions of the residential environment, experimental-based learning, teaching materials, and learning videos. It is recommended that Balinese subak local wisdom can continue to be maintained and other local wisdom can be implemented in learning models, teaching materials, and learning media.